Effect of Visual Information on Postural Control in Adults with Autism Spectrum Disorder - Lim, Y.; Lee, H.; Falkmer, Torbjorn; Allison, Garry; Tan, Tele; Lee, W.; Morris, Susan (Springer New York LLC, 2018)
© 2018 Springer Science+Business Media, LLC, part of Springer Nature Sensory processing difficulties affect the development of sensorimotor skills in individuals with autism spectrum disorder (ASD). However, the effect of sensory information on postural control is unclear in the ASD adult population. The present study examined the effect of visual information on postural control as well as the attentional demands associated with postural control in fourteen adults with ASD and seventeen typically developed adults. The results showed that postural sway and attention demands of postural control were larger in adults with ASD than in typically developed adults. These findings indicate that visual processing used for postural control may be different in adults with ASD. Further research in visual field processing and visual motion processing may elucidate these sensorimotor differences.